OVERVIEW OF WORK STRESS ON NGADA DISTRICT LAND OFFICE EMPLOYEES - Maria Fatima Egu; M. K. P. Abdi Keraf; R. Pasifikus Ch. Wijaya (Universitas Nusa Cendana, 2022)
Abstract. Work stress is a condition of the results of an individual's subjective imagination that can be an interaction between the individual and the work environment that can threaten and can put psychological, physiological and emotional stress on the individual. This study aims to find out the picture of work stress that includes symptoms of stress and the types of stress experienced by the Ngada District Land Office. This type of research is qualitative research with a phenomenological approach. The main informant amounted to 9 employees and 2 triangulations, namely the head of the Administrative Department and the head of the Land Law Relations Section. The results of the analysis showed the presence of work symptoms such as headaches, fever, feeling tired, diet and sleep patterns that became irregular, disappointed, and less satisfied with work. These results also showed the subjects were able to respond to stressful and stressful conditions with a healthier positive (eustres). Abstrak. Stres kerja adalah suatu kondisi dari hasil penghayatan subjektif individu yang dapat berupa interaksi antara individu dengan lingkungan kerja yang dapat mengancam dan dapat memberi tekanan secara psikologis, fisiologis dan sikap individu. Penelitian ini bertujuan mengetahui gambaran stres kerja yang meliputi gejala stres dan jenis-jenis stres yang dialami oleh pengawai Kantor Pertanahan Kabupaten Ngada. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologi. Informan utama berjumlah 9 pegawai dan 2 triangulasi yakni kepala Bagian Tata Usaha dan kepala Bagian Hubungan Hukum Pertanahan. Hasil analisis menunjukan adanya gejala kerja seperti sakit kepala, demam, merasa lelah, pola makan dan pola tidur yang menjadi tidak teratur, rasa kecewa, dan kurang puas dengan pekerjaan. Hasil ini juga menunjukan subjek mampu menyikapi kondisi-kondisi yang tekanan dan stres dengan lebih sehat positif (eustres).